2018
DOI: 10.1002/pd.5290
|View full text |Cite
|
Sign up to set email alerts
|

Trends in invasive prenatal diagnostic testing at a single institution

Abstract: Our study showed a significant decline in the number of amniocenteses, a steady increase in the percentage of abnormal results from invasive testing, and a decline in AMA as the sole indication for invasive testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…Unlike other authors [8][9][10][11][17][18][19], we did not observe a decline in invasive procedures neither after the introduction of NPSP with cFTS in 2007 or after the implementation of NIPT in 2013 [14], which suggests that the trends in our country do not reflect global changes in prenatal diagnosis. On the contrary, we observed a steady or even a slightly increased case load after 2007, which may be attributed to the increasing awareness of patients and doctors of the importance of prenatal diagnosis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike other authors [8][9][10][11][17][18][19], we did not observe a decline in invasive procedures neither after the introduction of NPSP with cFTS in 2007 or after the implementation of NIPT in 2013 [14], which suggests that the trends in our country do not reflect global changes in prenatal diagnosis. On the contrary, we observed a steady or even a slightly increased case load after 2007, which may be attributed to the increasing awareness of patients and doctors of the importance of prenatal diagnosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Meng et al (9.6%) [9] reported a similar rate of genomic abnormalities in their study, but they used both routine karyotyping as well as aCGH for genetic testing. Similarly, Awomolo et al in a recent study showed a high percentage of abnormal results, reaching 27% [19]. Nevertheless, the mode of testing was not stated in the paper and most likely comprised molecular genetics along with cytogenetics.…”
Section: Discussionmentioning
confidence: 85%